Self-efficacy and academic performance of vocational high school students - Ubaidillah, Fauzul Adim; Saifullah, Saifullah; Hitomi, Ahmad Rusli; Bulut, Sefa (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2023)
Abstract: The aim of this research is to examine the role of self-efficacy on academic performance of Vocational High School students. This research uses a quantitative approach with a correlational research design. The participants of this research are at 115 students of the Vocational High School, Department of Electrical and Industrial Engineering who were obtained based on convenience sampling technique. The data analysis is used by regression analysis with Jeffrey’s Amazing Statistics Program (JASP). The result of this research indicated that self-efficacy has a significant role on academic performance.Keywords: self-efficacy; academic performance; student